Developing an Accountable Budget Baseline for Infrastructure Projects: A Consolidated Cost and Schedule Estimation Framework and Maturity Assessment - Haryo Utomo Wisnu Nugroho; Silvianita Silvianita (Newinera Publisher, 2026)
Organizations frequently rely on multiple international references for cost estimating and schedule development, yet these references use different terminology, levels of detail, and emphases, which can leave budgeting stage estimation fragmented and difficult to audit. This paper develops a consolidated, stepwise framework by synthesizing prescriptive practices from PMI, AACE, NASA, and GAO, and applies the framework as an auditable process maturity assessment instrument. A benchmarking synthesis approach was used to screen candidate references for capital project relevance and explicit guidance for cost estimating and schedule development. Process steps were extracted, harmonized across sources, and consolidated into two aligned end to end process frameworks for cost estimating and schedule estimating. The consolidated steps were converted into assessment items, rated on a five level maturity scale, and summarized using achieved versus maximum scoring. Application to PT Pertamina Patra Niaga (PPN)’s budgeting stage practices indicates that the current cost estimating process reaches 56/70 (80%) maturity, while the current schedule estimating process reaches 46/90 (51%). The previous cost estimating process scores 43/70 (61%). The most prominent gaps relate to the formal documentation of ground rules and assumptions, typically captured in a Basis of Estimate, and to schedule model discipline, particularly coding, logic structure, and systematic schedule quality checks. Overall, the findings show that the framework is practical to implement and supports evidence based prioritization of process improvements toward more transparent, accountable, and reliable budgeting baselines for capital and infrastructure related investments.